1987
DOI: 10.1080/02724936.1987.11748469
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus neonatorum—experience with intrathecal serotherapy at Muhimbili Medical Centre, Dar es Salaam, Tanzania

Abstract: In an attempt to lower the mortality rate of neonatal tetanus a study was undertaken to determine whether intrathecal serotherapy influences mortality from this disease. Sixty-six babies with tetanus neonatorum were studied. The mortality rate among babies who received intrathecal anti-tetanus serum (ATS) was 45% compared with 82% in the control group given intramuscular ATS (P congruent to 0.002). Infants who received intrathecal ATS also had fewer complications than controls (P less than 0.001) and the durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…7 Opposite views came out in the studies of Bhandari which showed that intrathecal therapy lead to higher mortality than intramuscular therapy while Mongi showed that intrathecal therapy was superior to intramuscular in the treatment of neonatal tetanus. 8,9 Menon also observed the superiority of intrathecal treatment. 10 In 2004, Miranda-Filho and colleagues compared the efficacy of intramuscular HTIg (3,000 IU) plus intrathecal HTIg (1,000 IU) with intramuscular HTIg alone and found no significant difference in mortality.…”
mentioning
confidence: 91%
“…7 Opposite views came out in the studies of Bhandari which showed that intrathecal therapy lead to higher mortality than intramuscular therapy while Mongi showed that intrathecal therapy was superior to intramuscular in the treatment of neonatal tetanus. 8,9 Menon also observed the superiority of intrathecal treatment. 10 In 2004, Miranda-Filho and colleagues compared the efficacy of intramuscular HTIg (3,000 IU) plus intrathecal HTIg (1,000 IU) with intramuscular HTIg alone and found no significant difference in mortality.…”
mentioning
confidence: 91%
“…Administration of tetanus antitoxin using the intrathecal route offers a potential benefit in treating severe tetanus as tetanus toxin acts within the central nervous system (CNS). Case series and small randomized trials have reported large ( some >50%) improvements in mortality and hospital stay in both adults and neonates treated with intrathecal antitoxin 819 . However, most reports are of poor quality with large methodological differences and possible biases.…”
Section: Introductionmentioning
confidence: 99%
“…1980). Seven years later, Mongi concluded that ITS was superior to IMS in the treatment of neonatal tetanus (Mongi et al. 1987).…”
Section: Introductionmentioning
confidence: 99%